Solar Cell Transistor: A Solar Transistor and Photoferroelectric Memory (Adv. Funct. Mater. 17/2018). (23rd April 2018) - Pérez‐Tomás, Amador; Lima, Anderson; Billon, Quentin; Shirley, Ian; Catalan, Gustau; Lira‐Cantú, Mónica
Abstract : In article number1707099, Amador Pérez‐Tomás, Gustau Catalan, Mónica Lira‐Cantú and co‐workers present a solar transistor (or solaristor) core interface. The organic bulk heterojunction (a blend of polymers and fullerenes) efficiently harvests photon energy from the sun and splits photo‐generated excitons into free electron and holes. The perovskite oxide ferroelectric film acts as a switchable transparent electron transport layer with polarization state dependent tunable contact resistivity.